Pengaruh Asupan Nutrisi Dan Pola Makan Pada Pasien Dengan Sindrom Ovarium Polikistik - Shelly Lesmana; Gracia JMT Winaktu; Irene Maria Elena; Luciana Budiati Sutanto (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Polycystic Ovary Syndrome (PCOS) is a heterogeneous endocrine disorder that is commonly experienced by women of reproductive age worldwide. PCOS is one of the main causes of infertility with many complications such as insulin resistance, ovulatory dysfunction, and hyperandrogenism. Although it is one of the most common causes of infertility in women worldwide, nutritional management for patients with PCOS has not been studied in depth. Therefore, this literature review aims to evaluate and discuss the effect of nutritional intake and diet on PCOS patients. Overall, a low-carbohydrate diet with low-glycemic index and high-unsaturated fats is a good choice of nutritional intake for PCOS patients. In addition, the provision of micronutrient supplements can also play an important role in the nutritional management of PCOS patients.